2017
DOI: 10.1186/s12967-017-1356-8
|View full text |Cite
|
Sign up to set email alerts
|

Sprifermin (rhFGF18) modulates extracellular matrix turnover in cartilage explants ex vivo

Abstract: BackgroundSprifermin (recombinant human fibroblast growth factor 18) is in clinical development as a potential disease-modifying osteoarthritis drug (DMOAD). In vitro studies have shown that cartilage regenerative properties of sprifermin involve chondrocyte proliferation and extracellular matrix (ECM) production. To gain further insight into the process of sprifermin in the cartilage tissue, this study aimed at investigating the ECM turnover of articular cartilage explants in a longitudinal manner.MethodsBovi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
54
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 21 publications
0
54
0
Order By: Relevance
“…In the early phase of culturing, the chondrocytes of sprifermin-treated explants seemed to exhibit a catabolic phenotype, with decreased PIIBNP release and increased NITEGE release. The NITEGE release was previously seen in bovine articular cartilage, where it was suggested to be part of a coordinated process to expand the lacunae and allow proliferation of chondrocytes 12 . In the present study, it was not possible to monitor the temporal changes in cell proliferation.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…In the early phase of culturing, the chondrocytes of sprifermin-treated explants seemed to exhibit a catabolic phenotype, with decreased PIIBNP release and increased NITEGE release. The NITEGE release was previously seen in bovine articular cartilage, where it was suggested to be part of a coordinated process to expand the lacunae and allow proliferation of chondrocytes 12 . In the present study, it was not possible to monitor the temporal changes in cell proliferation.…”
Section: Discussionmentioning
confidence: 84%
“…To summarize, the cartilage explants permanently stimulated with sprifermin had continuously increased metabolic activity throughout the culture period (day 0-70). Duringearly-phase culturing (day 7-28) www.nature.com/scientificreports www.nature.com/scientificreports/ the explants had increased aggrecanase-mediated aggrecandegradation (NITEGE) and decreased type II collagen formation (PIIBNP), whereas the late-phase showed increased type II collagen formation.This investigation builds on a previous study that investigate the effect on human and porcine monolayer chondrocyte cultures 11 and bovine cartilage explants 12 . In current model we use OA human cartilage which is known to be more heterogenous than that of healthy bovine cartilage cultures.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…There have been numerous attempts to preserve or promote AC phenotype during in vitro culture of living AC, with varying degrees of success. Early studies in this field, employing mechanical loading systems and supplementation of media with growth factors, have demonstrated an anabolic effect and have explicated many of the key factors that regulate AC homeostasis (Fitzgerald et al, 2004;Guilak et al, 1994;Hall et al, 1991;Hascall et al, 1983a;Luyten et al, 1988;Sah et al, 1994;Sah et al, 1989). Towards the practical application of preserving implant properties prior to OCT procedures, these media formulations have been increasingly well defined, with some making their way to clinical and commercial application (Mickevicius et al, 2015;Teng et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…To that end, studies have recently shown that fibroblast growth factor 18 (FGF18) stimulates chondrocyte proliferation and matrix production in vitro and reduces AC degeneration and increases de novo matrix formation by osteoarthritic AC in vivo (Ellsworth et al, 2002;Moore et al, 2005). A recombinant version of this protein, known as sprifermin, currently a non-approved drug candidate and in clinical development for osteoarthritis treatment, also has positive effects in vitro, in vivo and in several recent pre-clinical and clinical trials in humans (Dahlberg et al, 2016;Lohmander et al, 2014;Mori et al, 2014;Power et al, 2014;Reker et al, 2017). Sprifermin decreases collagen type I expression in monolayer culture and decreases collagen type II expression at dosing concentrations > 100 ng/mL.…”
Section: Introductionmentioning
confidence: 99%